Manajemen Layanan Perpustakaan terhadap Loyalitas Mahasiswa pada Masa Pandemi Covid 19 - Sungadi Sungadi (Media Pustakawan, 2021)
During the covid-19 pandemic the library stopped all services that were in direct contact with users, so that the library was required to carry out new innovation services so that the information needs of the users were still met. Services that can be done are through online services where users can take advantage of the library's digital collection via the internet. The research on the theme of the effect of library service management on student loyalty was conducted to test the impact of library service management variables (X) on student loyalty (Y). The X variable is developed in 3 dimensions, namely the dimensions of library public policy (X1), loan transactions (X2) and online services (X3). Collecting data through distributing questionnaires to students at 3 private universities in Yogyakarta with the category A accredited university which has a student population of more than 25.000 people. Sampling was not using random sampling but by means of convenience sampling. Analyzing data through descriptive statistical testing and multiple regression. The results of multiple regression analysis partially and simultaneously library service management variables as well as the 3 dimensions X1, X2 and X3 affect student loyalty and from the correlation analysis of the dimensions contained in library service management variables to student loyalty variables it is proven that all hypotheses can be accepted. Conclusion: library service management during the pandemic which is responded to by students is a good (positive) phenomenon, so the respondent's appreciation of student loyalty is also good (superior).